Heavy quark potential and jet quenching parameter in a rotating D-instanton background - Jun-Xia Chen; De-Fu Hou (European Physical Journal C: Particles and Fields, 2024)
Abstract We obtain the dual gravity metric of rotating nuclear matter by performing a standard Lorentz transformation on the static metric in the D-instanton background. We then study the effects of the angular velocity, instanton density, and temperature on the heavy quark potential. The results show that the angular velocity and the temperature promote dissociation of the quark–antiquark pair, and the instanton density suppresses dissociation. Similarly, according to the results for the jet quenching parameter, we find that the parameter increases with the increase in angular velocity, instanton density, and temperature, and the jet quenching parameter in the rotating D-instanton background is larger than that of $$\mathcal {N} =4$$ N = 4 supersymmetric Yang–Mills (SYM) theory.